Manajemen Kurikulum Pendidikan Islam: Sinergi Antara Nilai Spiritual dan Inovasi Teknologi - Warsito, Warsito; Sunhaji, Sunhaji (Lembaga Intelektual Muda (LIM) Maluku, 2026)
The development of digital technology has brought significant changes to the education system, including Islamic education. The main challenge faced by Islamic educational institutions today is how to manage the curriculum effectively so that it remains based on Islamic spiritual values while also being responsive to technological innovations. This article aims to examine the concept of Islamic education curriculum management and analyze the importance of synergy between spiritual values and technological innovation in curriculum development. The writing method uses library research by analyzing various literature such as books, scientific journals, and relevant educational regulations. The study results show that effective management of the Islamic education curriculum should include planning, implementation, and evaluation of the curriculum integrated with Islamic values and the wise use of technology. The synergy between spiritual values and technological innovation can enhance the quality of learning, strengthen students' character, and maintain Islamic identity amidst the currents of globalization and the digitalization of education